Avaliação da qualidade de vida no trabalho: o caso da policia militar da cidade de João pessoa - PB - Melo, Marli Daiana da Silva (2014)
The aim of this study was to analyze the quality of life at work of police officers who work in the city of João Pessoa, state of Paraíba, Brazil. There is evidence that the way individuals perceive their life at work (satisfaction / dissatisfaction) can affect both their labor performance and their physical and mental health. According to Signorini (2000), although there are doubts as to the exact meaning of the term quality of life at work, the basic elements that distinguish them would be the concern with the effect of work on people and on the organizational effectiveness, as well as on the idea of participation in problem solving and organizational decision making. This dissertation is initially structured on a theoretical discussion about QLW and related topics, followed by methodological procedures adopted, results obtained and closing remarks. Although the research is classified as qualitative, quantitative data have been used in order to strengthen the results obtained. The survey instrument used was based on the structured Model of Walton, contemplating the categories of the Likert scale applied to police officers who work at the 1st and 5th Police Stations, which include the city of João Pessoa. It was found that in their perception, they are not satisfied with their quality of work life at work in all its aspects (dimensions), since the mean scores obtained in the Likert scale did not even exceed the value 4. Comparing the mean scores of the dimensions that make up the instrument of quality of work life with a cutout per battalion, we have that the mean scores generated by the officers of the 1st Battalion were always higher than the mean scores produced by the officers of the 5th Battalion. It was found also that the police officers who act as prison guards / custody of hospitals are those with poorer perceived quality of life at work.